Digital materialities
1 online resource (264 pages).
Keywords: As the distinction between the digital and the material world becomes increasingly blurred, the ways in which we think about design are also shifting and evolving. How can the human, digital and material be brought together to intervene in the world? What constitutes our digital-material environments? How can we engage with digital technologies to make sustainable, healthy and meaningful decisions, both now and in the future? Digital Materialities presents twelve chapters by scholars and practitioners working at the intersection between design and digital research in the UK, Spain, Australia and the USA. By incorporating in-depth understandings of the digital-material world from both the social sciences and design, the book considers how this combined knowledge might advance our capacity to design for the future. Divided into three parts, the focus of the book moves from the theoretical to the practical: how different digital materialities are imagined and emerge, through software emulation, urban sensors and smart homes; how new digital designs are sparked through collaborations between social scientists and designers; and finally, how digital design emerges from the insider work of everyday designers. A fascinating, ground-breaking book for students and scholars of digital anthropology, media and communication, and anyone interested in the future of digital design.